Effects of decreased Rac activity and malignant state on oral squamous cell carcinoma in vitro. - Yudai Matsuoka; Hani Al-Shareef; Mikihiko Kogo; Hirokazu Nakahara (PLoS ONE)
Rac proteins, members of the Rho family of small GTP-binding proteins, have been implicated in transducing a number of signals for various biological mechanisms, including cell cytoskeleton organization, transcription, proliferation, migration, and cancer cell motility. Among human cancers, Rac proteins are highly activated by either overexpression of the genes, up-regulation of the protein, or by mutations that allow the protein to elude normal regulatory signaling pathways. Rac proteins are involved in controlling cell survival and apoptosis. The effects of Rac inhibition by the Rac-specific small molecule inhibitor NSC23766 or by transfection of dominant negative Rac (Rac-DN) were examined on three human-derived oral squamous cell carcinoma cell lines that exhibit different malignancy grades, OSC-20 (grade 3), OSC-19 (grade 4C), and HOC313 (grade 4D). Upon suppression of Rac, OSC-19 and HOC313 cells showed significant decreases in Rac activity and resulted in condensation of the nuclei and up-regulation of c-Jun N-terminal kinase (JNK), leading to caspase-dependent apoptosis. In contrast, OSC-20 cells showed only a slight decrease in Rac activity, which resulted in slight activation of JNK and no change in the nuclei. Fibroblasts treated with NSC23766 also showed only a slight decrease in Rac activity with no change in the nuclei or JNK activity. Our results indicated that apoptosis elicited by the inhibition of Rac depended on the extent of decreased Rac activity and the malignant state of the squamous cell carcinoma. In addition, activation of JNK strongly correlated with apoptosis. Rac inhibition may represent a novel therapeutic approach for cancer treatment.